Trans-Z-source neutral point clamped inverter - Mo, W. (2013)
Transformer based Z-source (trans-Z-source) inverters are recently proposed by extending the traditional Z-source inverter with higher buck-boost capability as well as reducing the passive components at the same time. Multi-Level Z-source inverters are single-stage topological solutions used for buck-boost energy conversion with all the favourable advantages of multi-level switching retained. This paper presents three-level trans-Z-source Neutral Point Clamped (NPC) inverter topology, which achieves both the advantages of trans-Z-source and three-level NPC inverter configuration. With proper modulation scheme, the three-level trans-Z-source inverter can function with minimum of six device commutations per half carrier cycle (same as the traditional buck NPC inverter), while maintaining to produce the designed volt-sec average and inductive voltage boosting at ac output terminals. The designed topology and modulation control are tested by Matlab simulation and experimental laboratory prototype with captured results shown in the latter sections.